Monitoramento de parâmetros de qualidade da água na lagoa do Apodi/RN. - Silva, Manoel Mariano Neto da (Universidade Federal Rural do Semi-Árido, 2018)
Water resources have a wide variety of uses and are therefore of significant importance in relation to environmental, social, economic and biological issues. However, many factors contribute to the expansion of conflicts associated with water, among them, the degradation of surface and underground reservoirs, population growth and rising consumption levels. These conditions become even more aggravating when discussed in the semiarid context, due to the high population density, the low rainfall and the irregular distribution of rainfall. Through these notes, this work had the general objective to monitor the water quality in the Apodi / RN Lagoon. For this purpose, field surveys were carried out for the purpose of physicochemical analysis, using a multi-parameter analysis probe, model HORIBA U-50, which allows to quantify in situ instantaneously the following parameters the Hydrogenion potential, Turbidity, Temperature, Dissolved Oxygen, Electrical Conductivity, Total Dissolved Solids, Salinity, Oxidation Potential and Percent of Dissolved Oxygen. The analyzes were performed monthly, in the period corresponding to the months of January to December of 2017, in 4 distinct points, in order to total 48 samples per parameter. The values obtained were compared with the legislation in force. It was verified that the highest temperatures were recorded in February, although this is the month with the highest rainfall intensity, and the lowest values occurred in May. The electrical conductivity did not show significant variations, which contributed to the fact that the values recorded were close to the mean, in this case, a discrepancy value of 9.99 mS / cm was observed in the month of October. The oxidation potential also presented values with little variation and the only value considered abnormal occurred in January, when a potential of -250 mV was identified. It is observed that the CONAMA resolution 357/2005 was partially met, due to the fact that two values were shown above the value stipulated by the normative when analyzing the data referring to the dissolved oxygen. Regarding the electrical conductivity, it is verified that this indicative points to conditions of degradation of water quality, according to CETESB notes. As for the total dissolved solids, when compared with the literature, they presented values similar to those recorded in other water bodies in the semiarid region.
Artigo Acadêmico
Keywords: Recursos hídricos; Semiárido; Parâmetros físico-químicos; ENGENHARIAS::ENGENHARIA SANITARIA